2020
DOI: 10.3346/jkms.2020.35.e71
|View full text |Cite
|
Sign up to set email alerts
|

Reflex and Spontaneous Movements in Adult Patients during the Process of Determining Brain Death in Korea

Abstract: Background: Brain death is a clinical diagnosis that implies irreversible loss of function of the entire brain, including the brainstem and both hemispheres. Based on previous reports, it is not rare for reflex and spontaneous movements to occur in patients during the process of determining brain death. However, reports of the frequency and common types of these movements vary from study to study. Thus, we evaluated adult patients with impending brain death in Korea to determine the frequency and characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…They reported that the most common reflex was the plantar extension and flexion response to painful stimuli, which were observed in 30 of the participating patients. 3 Beckman et al evaluated 144 patients diagnosed with brain death and showed that 32 patients, in whom toe fluctuations, increased deep tendon reflexes, Lazarus sign, arm-neck flexion, fasciculations, and finger twitches were observed, had spontaneous and spinal reflexive movements. 4 In a study conducted by Conci et al, viscero-visceral and viscero-somatic reflexes were investigated and the authors observed a contraction response in the abdominal muscles during the peritoneal incision in 15 of the 25 patients, who underwent laparotomy for donor nephrectomy,.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the most common reflex was the plantar extension and flexion response to painful stimuli, which were observed in 30 of the participating patients. 3 Beckman et al evaluated 144 patients diagnosed with brain death and showed that 32 patients, in whom toe fluctuations, increased deep tendon reflexes, Lazarus sign, arm-neck flexion, fasciculations, and finger twitches were observed, had spontaneous and spinal reflexive movements. 4 In a study conducted by Conci et al, viscero-visceral and viscero-somatic reflexes were investigated and the authors observed a contraction response in the abdominal muscles during the peritoneal incision in 15 of the 25 patients, who underwent laparotomy for donor nephrectomy,.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of movements including RMs and SMs observed in PWIBDs has reportedly ranged from 17.0% to 75.0%. 3 5 9 10 11 12 13 SMs reflect brain function while RMs reflect the function of the spinal cord, and so SMs do not appear in patients confirmed as brain death, whereas RMs such as spinal reflexes may appear in them. 2 14 A multicenter study conducted in Argentina applied a standardized protocol of stimuli to elicit reflexes in PWIBDs before and after performing apnea tests in 107 PWIBDs, and observed various types of RMs.…”
Section: Discussionmentioning
confidence: 99%
“…The present authors previously performed a prospective study that examined the RMs and SMs observed in 436 PWIBDs during the decision process about brain death. 5 The present study excluded 22 of those 436 PWIBDs, and so enrolled 414 PWIBDs who were the objects of the previous research. Sixteen of the 22 excluded PWIBDs had missing information on hypertension, diabetes mellitus, cardiac disease, smoking, and alcohol drinking, while the other 6 patients were excluded since the causative disease for brain death was not appropriate or there was only 1 case for 1 etiology: the KODA registry described the etiology of brain death as arteriovenous malformation, brain abscess, diffuse astrocytoma, encephalopathy, toxic encephalopathy, and unruptured aneurysm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations